SORPTION OF COPPER (II), NICKEL (II) AND COBALT (II) IONS INTO THE IONITE MODIFIED BY POLYPHINYLCHLORIDE AND POLYETHYLENE POLYAMINE (Scientific journal of the Fergana State University, 2023)
Polyphinylchloride was modified by polyethylene polyamine, and the ionites were studied in static conditions by the artificial solution of copper (II), nickel (II) and cobalt (II) ions. In static conditions, factors affecting the sorption process, such as time, temperature and concentration dependence were investigated. The results of the inquiry process were studied by IR analysis